Táctica de política. Pequeños cambios para mejorar la gerencia pública - Meza, Oliver; Moreno Jaimes, Carlos (El Colegio de México A.C., 2018)
An extensive bibliography highlights the political, budgetary and organizational difficulties that public administration faces in Mexico. However, existing ways to overcome these challenges have not been examined in a systematic or sufficient manner. What kind of actions do public managers have available to them to increase the effectiveness of the programs they administer? In this article, we identify a form that we have been calling policy tactics, which allow public managers to take advantage of interaction between citizens and state agents to use bureaucratic discretion to make the policy more effective. The article seeks to define policy tactics, illustrate using a real case study how these are observed in practice, and offer alternative ways to improve the effectiveness of policies, using the discretion available to operators in an instrumental manner.